HUBUNGAN KARAKTERISTIK INDEKS GEOMORFIK TERHADAP KEMUNCULAN MANIFESTASI PANAS BUMI DI DAERAH NOKILALAKI - Muhammad Hudzaifah; Nana Sulaksana; Dewi Gentana (PPSDM Geominerba, 2021)
The appearance of geothermal manifestations in the Nokilalaki area is related to the morphology and geological structure which is influenced by the tectonic activity of the Palu - Koro segment. The study of geomorphic index through the calculation of river branching ratio (Rb), mountain face sinusitis (Smf), valley bottom width ratio - height (Vf) and lineament density (Ld) to determine the relationship of geomorphic index characteristics to the appearance of geothermal manifestations. The research method is remote sensing analysis and geomorphic index analysis on the Indonesian Topographical Map (RBI) and ASTER – DEM images to obtain the main pattern of geological lineaments and geomorphic index values. The value of the geomorphic index describes the level of tectonic activity and permeability in rocks, which plays a role in generating geothermal fluid from a geothermal system at depth to the surface. Based on the combination of geological lineament maps, geomorphic index maps and distribution of geothermal manifestations, the study area has two groups of geothermal manifestations. The area with the main pattern of geological lineament trending northwest – southeast is an area that is not deformed (Rb value: 4.55), active tectonic activity (Smf value: 1.34 – 1.53), high uplift (Vf value: 0.47), low lineament density (Ld value: 0.49 – 0.91), is associated with the appearance of geothermal manifestation groups in the depression edge of the Palu - Koro fault segment in the center of the study area. The main patterned area of ​​the north- northeast-south-southwest geological lineament is a non-deformed area (Rb value: 4, 20), active tectonic activity (Smf value: 1.47), high uplift (Vf value: 0, 22), medium to high lineament density (Ld value: 1.37 – 2.75), associated with the emergence of groups of geothermal manifestations in the hilly area of ​​the edge of the Palu - Koro fault segment in the southwest part of the study area.